Over-the-catheter retrieval of a retained microcatheter following Onyx embolization: a technical report. (16th June 2011) - Newman, C Benjamin; Park, Min S; Kerber, Charles W; Levy, Michael L; Barr, John D; Pakbaz, R Sean
Abstract : Background: Brain arteriovenous malformations are vascular lesions that are increasingly being treated with endovascular embolization. A potential complication with endovascular embolization is microcatheter entrapment within the embolic material. In the present report, a novel technique for the retrieval of microcatheters retained during Onyx embolization of intracranial lesions is described. Clinical presentation: Two patients (one boy and one girl, aged 13 and 15 years, respectively) with arteriovenous malformations (one unruptured, one ruptured; Spetzler–Martin grades 4 and 3) presented for embolization. Intervention: During Onyx 18 embolization of the arteriovenous malformations, Echelon-10 microcatheters became entrapped into the arterial feeders by casts of the Onyx. Initial attempts to remove the microcatheters by traction were unsuccessful. The hubs of the microcatheters were transected and Concentric Medical Outreach distal access catheters were then advanced over the microcatheters and positioned at the proximal aspects of the microcatheter-Onyx plugs. Using the Outreach catheters for countertraction, the Echelon-10 microcatheters were then successfully released from the Onyx plugs under fluoroscopic visualization without significant distortion of the arteries. There were no complications related to the microcatheter extractions. Conclusions: A novel technique, which may be useful in the removal of retained microcatheters during Onyx embolization of Brain arteriovenous malformations, is presented.